Genetic background of Meniere’s disease (Journal of Medical Science, 2018)
Meniere’s disease (MD) as an inner ear disorder including such symptoms as recurrent vertigo attacks, tinnitus, fluctuating or progressive sensorineural hearing loss. Its relatively frequent familial incidence implicates a genetic background. An autosomal dominant inheritance was commonly observed with a few exceptions. It was established that Meniere’s disease is not a monogenic disorder. Instead a group of genes of genomic and mitochondrial genes was established as determinants of hearing loss. Another group of genes was associated with inner ear (vestibulum, labyrinth, endolymph) alterations followed by dizziness and tinnitus. Altogether, many studies suggest a multigenic interaction to predispose to develop Meniere’s disease.